Association Between Novel Pro- and Anti- Inflammatory Adipocytokines in Patients with Acute Coronary Syndrome. (September 2022) - Wei, Chen; Liu, Yixiang; Xing, Enhong; Ding, Zhenjiang; Tian, Yanan; Zhao, Zhuoyan; Fan, Wenjun; Sun, Lixian
Background and aims: Novel pro- and anti-inflammatory adipocytokines affect inflammation, energy metabolism, and insulin signaling. However, their role in acute coronary syndrome (ACS) development is unclear. We evaluated the diagnostic and risk predictive value of such adipocytokines for ACS. Methods: We enrolled 168 consecutive inpatients with suspected ACS and detected serum PLIN1, PLIN2, PLIN5, CTRP6, CTRP7, CTRP11, WISP1, FAM19A5, TNF-α, and adiponectin levels. Multivariate logistic regression analysis and Spearman's test were used to assess risk factors for ACS and correlations between serum adipocytokines and continuous variables, respectively. Results: Serum levels of the adipocytokines differed between ACS and Non-ACS groups ( p < 0.05). After adjusting for confounding factors, serum PLIN1, PLIN2, PLIN5, CTRP6, CTRP7, CTRP11, WISP1, and FAM19A5 levels were independently associated with ACS ( p < 0.05). Increasing tertiles of serum PLIN1, PLIN2, CTRP7, CTRP11, and WISP1 levels increased the ACS risk, which decreased gradually with increasing PLIN5 and CTRP6 tertiles ( p for trend <0.05). Serum PLIN1, PLIN5, CTRP6, CTRP7, CTRP11, WISP1, and FAM19A5 levels correlated with ACS severity. Conclusions: PLIN1, PLIN2, CTRP7, CTRP11, and WISP1 were identified as independent ACS risk factors, whereas PLIN5, CTRP6, and FAM19A5 were independent protective factors for ACS. These serum adipocytokines are novel potential clinical biomarkers of ACS.